Synthesis and characterization of magnetic titanium dioxide nanoparticles, Fe-TiO2 NPs for adsorption of lead ion / Nurul Syuhada Zulhilmi - Zulhilmi, Nurul Syuhada (2019)
Titanium dioxide nanoparticles, TiO2 NPs were synthesized by green synthesis using banana peel extract while magnetic TiO2 nanoparticles, Fe-TiO2 NPs were synthesized by a co-precipitation method using FeSO4.7H2O. The obtained TiO2 NPs and Fe-TiO2 NPs have been characterized using FTIR, XRD and FESEM- EDX. The hydroxyl and carbonyl group present in banana peel extract were responsible for the formation of highly stable TiO2 NPs in FTIR analysis. The absorption band decreased in Fe-TiO2 NPs because TiO2 NPs were reduced when synthesizing Fe-TiO2 NPs. XRD pattern for both NPs showed a similar result which indicated the formation of anatase phase of titanium dioxide. TiO2 NPs and Fe-TiO2 NPs were also characterized by FESEM under electron microscopy with 50 Kx and 80 Kx magnifications respectively. FESEM micrograph of TiO2 NPs shows a spherical shape bonded to each other while Fe-TiO2 NPs aggregated with spherical shape particles. The average diameter of Fe-TiO2 NPs was found to be around 26.08 nm confirming that the synthesized Fe-TiO2 NPs was in the nanometer range. The adsorption efficiency of heavy metal ion (lead ion) in the adsorption process at various experimental parameters such as pH, initial concentration of Pb(NO3)2 solution and adsorbent dosage were investigated. Desorption process of lead ion has been conducted at optimum parameters for different eluents, HCl and CH3COOH. The extent of adsorption efficiencies and desorption efficiency by Fe-TiO2 NPs were characterized using AAS. The optimum removal for lead ion was obtained at pH 5, 50 ppm concentration of Pb(NO3)2 solution and 0.04 g adsorbent dosage. HCl was the best eluent showed a higher desorption efficiency than CH3COOH. The application of Fe-TiO2 NPs was tested at lake water sample in UiTM Kuala Pilah and was found that adsorption process occurred at acidic condition. From the test conducted, the amount of Pb2+ ions exceeds the acceptable value standard of 0.05 ppm. The lake water was contaminated with Pb2+ ions that will come from various sources.